Immobilization of a Plant Lipase from Pachira aquatica in Alginate and Alginate/PVA Beads - Bonine, Barbara Martineli [UNESP]; Polizelli, Patricia Peres; Bonilla-Rodriguez, Gustavo Orlando [UNESP] (Hindawi, 2014)
This study reports the immobilization of a new lipase isolated from oleaginous seeds of Pachira aquatica, using beads of calcium alginate (Alg) and poly(vinyl alcohol) (PVA). We evaluated the morphology, number of cycles of reuse, optimum temperature, and temperature stability of both immobilization methods compared to the free enzyme. The immobilized enzymes were more stable than the free enzyme, keeping 60% of the original activity after 4 h at 50°C. The immobilized lipase was reused several times, with activity decreasing to approximately 50% after 5 cycles. Both the free and immobilized enzymes were found to be optimally active between 30 and 40°C.